2008
DOI: 10.1007/s00405-008-0645-5
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage graft in type I tympanoplasty: audiological and otological outcome

Abstract: The aim of this study is to evaluate anatomical and audiological results of cartilage tympanoplasty compared to fascia tympanoplasty in the reconstruction of tympanic membrane perforations. We carry a retrospective study about 380 patients operated in our department between 1998 and 2005. Patients were classified into two groups: 90 (23.6%) undergo cartilage tympanoplasty and 290 (76.4%) fascia tympanoplasty. In each group, we calculated the average of pre and postoperative air bone gap (ABG) and the average a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 20 publications
3
49
0
3
Order By: Relevance
“…In this 380-patient study, they found that there were no anatomical and functional differences between the two groups. Based on these similar results, they suggested that using cartilage was the first choice in tympanoplasties (16).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In this 380-patient study, they found that there were no anatomical and functional differences between the two groups. Based on these similar results, they suggested that using cartilage was the first choice in tympanoplasties (16).…”
Section: Resultsmentioning
confidence: 81%
“…Similar ratios were also obtained in the study by Karaman et al (15). Ben Gamra et al (16) anatomically and audiologically compared the patients undergoing cartilage and fascia tympanoplasty. In this 380-patient study, they found that there were no anatomical and functional differences between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…These results are similar to Gamra et al where they observed good functional hearing results (ABG <20 dB) in 89% with cartilage graft and 82.8% with temporalis fascia graft (p >0.005). 19 The current study suggests that palisade cartilage graft and temporalis fascia graft for tympanic membrane perforation closure are comparable. The disadvantage of using thicker cartilage, thought to interfere with hearing and sound conduction, was overcome by slicing them to achieve a thickness comparable with that of the temporalis fascia.…”
Section: Air Bone Gap Closurementioning
confidence: 90%
“…Timpanik membranın perforasyonunun onarımında greft materyali olarak değişik greft materyalleri kullanılmışsa da en sık kullanılan greft materyalleri temporal kas fasyası ve perikondriumdur (3)(4)(5)(6)(7)(8). Temporal kas fasyası 1950'lerden beri kullanılan kullanımı ve elde edilmesi kolay bir greft materyalidir (5-7).…”
Section: Discussionunclassified
“…Timpanoplastide timpanik membran perforasyonunun onarımı için temporal kas fasyası, perikondrium ve kartilaj gibi dokular değişik teknikler uygulanarak kullanılmaktadır (1)(2)(3). İlerlemiş orta kulak patolojileri, retraksiyon poşlarının varlığı ve atelektatik kulaklarda greft materyali olarak kullanılan temporal kas fasyasının atrofiye olma olasılığı fazla olduğu için bu tür vakalarda perikondrium kullanılmasının daha uygun olacağı yönünde yayınlar her geçen gün artmaktadır (4).…”
Section: Introductionunclassified